Efficacy of the Mercedes‐Benz closure technique for vaginal reconstruction in female robot‐assisted radical cystectomy. Issue 1 (17th July 2022) - Sasaki, Yutaro; Takahashi, Masayuki; Hashimoto, Keisuke; Fukuta, Kyotaro; Shiozaki, Keito; Daizumoto, Kei; Ueno, Yoshiteru; Tsuda, Megumi; Kusuhara, Yoshito; Fukawa, Tomoya; Yamaguchi, Kunihisa; Yamamoto, Yasuyo; et al.
Abstract: Introduction: Vaginal reconstruction using the posterior vaginal wall is required following radical cystectomy in women with resection of the uterus, adnexa, and anterior vaginal wall. Roll closure and clamshell closure are two widely known techniques. Of these, clamshell closure is recommended because roll closure has a high likelihood of breakdown or a resultant canal that is too narrow for sexual intercourse. In clamshell closure, however, folding the posterior vaginal wall anteriorly can be difficult. Therefore, we devised Mercedes‐Benz closure, in which the vaginal wall is sutured from three directions to form a Mercedes‐Benz shape, for anastomosis without tension on the vaginal wall. The present study was performed to investigate the efficacy of this alternative surgical technique for vaginal reconstruction. Methods: Twenty‐six patients who underwent vaginal reconstruction following robot‐assisted radical cystectomy were divided into two groups: 15 underwent clamshell closure and 11 underwent Mercedes‐Benz closure. The patients' characteristics and surgical outcomes were compared between the two groups. Results: There were no significant differences in clinical characteristics, including age, body mass index, and prior abdominal surgery between the two groups. The median vaginal reconstruction time tended to be longer in the Mercedes‐Benz closure group than in the clamshell closure group (35.0 vs. 27.0 min, p  = 0.102). No complications associated with vaginal reconstruction were identified. Conclusion: The surgical outcomes were comparable between Mercedes‐Benz closure and clamshell closure. If vaginal reconstruction with clamshell closure is difficult, Mercedes‐Benz closure is a valuable alternative technique.